Normative data for the lower extremity functional scale (LEFS). (4th July 2017) - Dingemans, Siem A; Kleipool, Suzanne C; Mulders, Marjolein A M; Winkelhagen, Jasper; Schep, Niels W L; Goslings, J Carel; Schepers, Tim
Abstract : Background and purpose — The lower extremity functional scale (LEFS) is a well-known and validated instrument for measurement of lower extremity function. The LEFS was developed in a group of patients with various musculoskeletal disorders, and no reference data for the healthy population are available. Here we provide normative data for the LEFS. Methods — Healthy visitors and staff at 4 hospitals were requested to participate. A minimum of 250 volunteers had to be included at each hospital. Participants were excluded if they had undergone lower extremity surgery within 1 year of filling out the questionnaire, or were scheduled for lower extremity surgery. Normative values for the LEFS for the population as a whole were calculated. Furthermore, the influence of sex, age, type of employment, socioeconomic status, and history of lower extremity surgery on the LEFS were investigated. Results — 1, 014 individuals fulfilled the inclusion criteria and were included in the study. The median score for the LEFS for the whole population was 77 (out of a maximum of 80). Men and women had similar median scores (78 and 76, respectively), and younger individuals had better scores. Participants who were unfit for work had worse scores. There were no statistically significant correlations between socioeconomic status and type of employment on the one hand and LEFS score on the other. A history of lower extremity surgery was associated with a lower LEFS score. Interpretation — High scores were observed for the LEFS throughout the whole population, although they did decrease with age. Men had a slightly higher score than women. There was no statistically significant correlation between socioeconomic status and LEFS score, but people who were unfit for work had a significantly worse LEFS score.